Attitude, perceived behavioral control and intention to participate in gig economy: the role of push motivation / Wong Yun-Tinn … [et al.] - Yun-Tinn, Wong; Jin-Kang, Hon; Yi-Xuan, Loh; H.N, Au Yong (2023)
In this paper, the central theorem is to examine factors that influence Malaysians aged from 18 to 40 years old to join the Gig Economy in the expansion of the Gig Economy. There will be five (5) independent variables derived from the Theory of Planned Behavior (TPB) and Push and Pull Theory (PPT), such as Attitudes (ATT), Perceived Behavior Control (PBC), Subjective Norm (SN), Pull Motivation (PLM), and Push Motivation (PSM). This paper utilized a primary data approach with a voluntary sampling method to collect 462 sample sizes via Google Forms. Furthermore, the data analysis part employed IBM SPSS Statistics software. In the group comparison, age group, race, and living status showed significant differences. The model is free from multicollinearity, autocorrelation, and heteroscedasticity problems. Among selected independent variables (IV), only Attitudes (ATT), Perceived Behavior Control (PBC), and Push Motivation (PSM) are significant in explaining the influence of the factors affecting Malaysians aged 18 to 40 years old to participate in the Gig Economy. The imbalance ratio of the Malaysian population by ethnicity is shown in this study. For business, the organizations could furnish a hiring structure aligned to the current labor market trend, for instance, budget allocation for skill enhancement for their employees. Next, the results showed that the absence of job security is not a factor that prevents individuals from participating in the Gig Economy. However, from the policymaker's perspective, job security should still be enhanced through advanced rules and regulations of the Gig Economy. Applying the theory of planned behavior, and push and pull theory, this study focuses on the youth segment who are generally tech-savvy in determining the intention of the youth to participate in the gig economy.